Dynamic RF Optimization: Advanced Wi-Fi Resource and Radio Management Algorithms for Network Performance Enhancement - Prasad Danekula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the evolution and implementation of advanced radio frequency (RF) optimization techniques in modern wireless networks, focusing on dynamic resource and radio management algorithms. The article examines core radio management algorithms, including Dynamic Frequency Selection, Quality of Service management, and channel bonding technologies, particularly in the context of wifi (802.11) technology. The article investigates various implementation considerations, addressing network density challenges, environmental interference, user demand patterns, and resource allocation strategies. Performance benefits are analyzed across multiple dimensions, including speed optimization, latency reduction, reliability improvements, and capacity enhancement, with particular attention to AI and machine learning applications. The article also evaluates different application environments, from enterprise deployments to public spaces, examining their unique challenges and solutions. Furthermore, the article explores future implications for wireless networks, considering emerging technologies, scalability considerations, and integration with next-generation wireless standards, providing insights into the transformative role of artificial intelligence in network optimization and management.